Mixed layer depth reconstructions based on dinocyst assemblage data of sediment core HU91-045-072 - Xiner Wu; Anne de Vernal; Estelle Allan (PANGAEA, 2025)
Winter mixed layer depth (MLD) was reconstructed from the dinocyst assemblage data of sediment core HU91-045-072 using two different approaches: modern analogue technique (MAT) and weighted averaging partial least square (WAPLS) regression and calibration. The n = 1968 modern dinocyst database and the modern MLD climatology of 1981-2010 from the World Ocean Atlas 2018 were used as calibration dataset.
In: Wu, X et al. (2025): Mixed layer depth reconstructions based on dinocyst assemblage data for 16 Holocene records in the subpolar North Atlantic using the modern analogue technique and weighted averaging partial least squares [dataset publication series]. PANGAEA, https://doi.org/10.1594/PANGAEA.982394